Implementasi Program Dinas Sosial Kota Palu Dalam Pemberdayaan Penyandang Disabilitas; Studi Kasus Rumah Singgah Nompeili Ntodea Kota Palu - Febryanti, Feby; Syamsuri, Syamsuri; Pangeran, Ismail (Journal of Islamic Community and Development, 2025)
This study aims to analyze the role of the village government in developing the potential of young people in Ogobayas Village, Mepanga Subdistrict, Parigi Moutong Regency. Young people are an important asset in village development, so developing their potential is one of the main focuses of the village government. This study is a field study using a descriptive qualitative approach. The sampling technique used is purposive sampling. Data collection techniques include observation, interviews, and documentation. The research findings indicate that the village government has implemented various programs and activities aimed at enhancing the role of the village government in developing the potential of young people in Ogobayas Village, Mepanga Sub-district, Parigi Moutong Regency, with a primary focus on sports and religious activities. These efforts are realized through the provision of adequate sports facilities, the organization of tournaments and training, and support for religious activities such as regular religious study sessions and celebrations of Islamic holidays. As a result, it is hoped that the youth of Ogobayas Village can develop holistically, both physically and spiritually, and contribute positively to the progress of the village.